1999
DOI: 10.1080/02791072.1999.10471727
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Management in Persons with Co-Occurring Psychiatric and Substance Use Disorders

Abstract: Persons presenting with concurrent psychiatric and substance problems present unique challenges for diagnosis and for effective and rational treatment planning. This is especially true for psychiatrists attempting to prescribe pharmacologic interventions which will promote recovery from both disorders and improve function. In order to be effective in this endeavor it is important to have a clear understanding of the dynamics of addiction as well as the particular issues and struggles related to mental illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Recovering persons who have dual diagnoses may be influenced by 12-steporiented treatment staff or self-help groups to avoid taking their medication (14). Substance users may decline medication because of denial of illness, preferring to ascribe their symptoms solely to substance misuse rather than to mental illness because the latter is more stigmatizing; medication, even if accepted initially, is used only temporarily (13,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recovering persons who have dual diagnoses may be influenced by 12-steporiented treatment staff or self-help groups to avoid taking their medication (14). Substance users may decline medication because of denial of illness, preferring to ascribe their symptoms solely to substance misuse rather than to mental illness because the latter is more stigmatizing; medication, even if accepted initially, is used only temporarily (13,15).…”
mentioning
confidence: 99%
“…Substance misuse can directly impair judgment about health behaviors (11,12). Substance abuse may function as self-medication, supplanting the use of psychiatric medications that may be perceived as less effective, slow to act, or having more side effects (13). Recovering persons who have dual diagnoses may be influenced by 12-steporiented treatment staff or self-help groups to avoid taking their medication (14).…”
mentioning
confidence: 99%
“…For example, there is significant disparity between official recommendations to avoid benzodiazepines in the treatment of co-occurring psychiatric and substance use disorders 9 and actual clinical practice where benzodiazepines are commonly prescribed. 10 Although several papers have been written about the challenges of prescribing to patients with co-occurring psychiatric and substance use disorders, 11,12 there seem to be ongoing biases that affect these prescribing practices. For example, a recent survey reported that psychiatrists underutilized psychological and psychoeducational measures when prescribing to patients with concurrent addiction and schizophrenia in contrast to schizophrenia alone.…”
Section: Introductionmentioning
confidence: 99%
“…The unsettling experience of feeling like he or she might be harming the patient or colluding with the patient's addictive pathology can contribute to significant anxiety about prescribing. One common response is to under-prescribe 11,12 in an effort to avoid feeling that one is harming the patient. 16 Additional factors that may contribute to under-prescribing are the sense of helplessness or betrayal that clinicians experience when confronted with the power of the addictive drugs in contrast to the "weak" prescribed medications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation